2013
DOI: 10.3390/ijms140715141
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of pr-10a Overexpression at the Molecular and the Phenotypic Level

Abstract: Biotechnological approaches using genetic modifications such as homologous gene overexpression can be used to decode gene functions under well-defined circumstances. However, only the recording of the resulting phenotypes allows inferences about the impact of the modification on the organisms’ evolutionary, ecological or economic performance. We here compare a potato wild-type cell line with two genetically engineered cell cultures homologously overexpressing Pathogenesis Related Protein 10a (pr-10a). A detail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 72 publications
1
9
0
Order By: Relevance
“…3b ). We also identified an up-regulated homolog ( c51305.g_c0 ) of tyrosine aminotransferase (TAT) gene known for SA synthesis, and an up-regulated pathogen-related gene PR-10 homolog ( c67327.g_c0 ) in the SA pathway, consistent with that reported previously 49 . The homolog of transcription factor TGA known to be involved in the SA pathway 50 was down-regulated.…”
Section: Resultssupporting
confidence: 89%
“…3b ). We also identified an up-regulated homolog ( c51305.g_c0 ) of tyrosine aminotransferase (TAT) gene known for SA synthesis, and an up-regulated pathogen-related gene PR-10 homolog ( c67327.g_c0 ) in the SA pathway, consistent with that reported previously 49 . The homolog of transcription factor TGA known to be involved in the SA pathway 50 was down-regulated.…”
Section: Resultssupporting
confidence: 89%
“…Expectedly [30], on some substrates respiration was detected by phenotype microarray analysis even though these substrates did not sustain growth.…”
Section: Classification and Featuresmentioning
confidence: 99%
“…Proteome analysis demonstrated that roots of Pisum sativum, a salinity-tolerant peanut callus cell line, had significantly elevated concentrations of PR-10 protein [36] as did salt-tolerant barley [21]. Overexpression of potato PR-10a gene in potato suspension cells and PR-10a gene from Jatropha curcas in tobacco exhibited significantly increased salt and osmotic tolerance [37,38]. Most PR proteins are induced through the plant hormones in addition to abiotic stress such as salt and drought and biotic stressors such as pathogens [39].…”
Section: Gene Expression Of Ros-scavenging Enzymes and Preferentiallymentioning
confidence: 99%